Genetic Aspects of Dentinogenesis Imperfecta - Elza Ibrahim Auerkari; Hedijanti Joenoes (Faculty of Dentistry, Universitas Indonesia, 2015)
Dentinogenesis Imperfecta (DI) is a hereditary, simple autosomal dominant disorder showing abnormalities in the dentin of the developing teeth and occurring at a rate of about 1 in 8000 births. The expression of DI shows a high penetrance and a low mutation rate. Two main types of DI appear to exist: type I which is the defect associated with osteogenesis imperfecta, and type II which is the classical hereditary opalescent dentin. The formerly proposed DI type III appears to be only a modified expression of the same gene as in the classical DI type II. Any gene therapy type of treatment is unrealistic for adolescent patients who already exhibit the symptoms. However, there is a good prospect for early screening since DI is inherited as a dominant disorder, and known trail from parents or siblings is a strong indication for later exposure to DI. At present there are no practical means to correct the genetic defect or to avoid the symptoms. Nevertheless, screening provides an early warning and helps to guide protective and restorative treatment so early that maximum amount of the natural dentition can be retained.